Psychological burnout syndrome in elementary school teachers in metropolitan Lima - Fernández, Manuel (2002)
This research studies the psychological burnout syndrome on a sample of 264 elementary school teachers. Three components of the syndrome are analyzed: emotional exhaustion, depersonalization and lack of self-fulfillment. Results indicate that 43% of teachers are prone to develop the syndrome in a short lapse of time. The components of the syndrome are discussed and related to sociodemographic variables in which the teachers are immersed.